Sistem lahan basah buatan untuk mereduksi sedimen dan polutan di Sungai Tougela Kabupaten Minahasa - La’la Monica; Liany Amelia Hendratta; Olivia Maria Tumurang (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Lake Tondano, a national priority lake, has experienced increasing sedimentation and declining water quality due to sediment and pollutant loads from its inlet rivers, including the Tougela River. Agricultural activities, settlements, and hydrological conditions contribute significantly to elevated sediment and nutrient inputs, particularly phosphate, which threaten the sustainability of the lake ecosystem. This study aims to analyze flood flow characteristics, sedimentation, and water quality of the Tougela River, as well as to evaluate the application of constructed wetlands as a measure to control sediment and pollutant loads before entering Lake Tondano. The research method includes hydrological analysis using the rational method to estimate design flood discharge, analysis of suspended sediment concentration, and water quality assessment based on BOD, COD, and phosphate parameters. Data were obtained through field measurements, water sampling, and rainfall data analysis. A floating constructed wetland was applied with emergent plants, planting media and floating media made of bamboo and anchors. The selected emergent plants were local aquatic macrophytes, namely water hyacinth (Eichornia crassipes) and water spinach (Ipomoea aquatica) which are available at the research site. The results indicate that sedimentation in the Tougela River reaches 160.95 g/s at the 50-year return period flood discharge. BOD and COD values comply with water quality standards, while phosphate concentrations only meet Class III–IV standards. The constructed wetland reduced phosphate concentrations by 10–24.5% and suspended sediment by 4.6%. The water flow in the floating constructed  wetland was still influenced by the lake’s water flow, which affected the observation results, but its application has the potential as a nature-based solution for reducing sediment and pollutant loads.